2017
DOI: 10.1128/jvi.00584-17
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Dependent Anion Channel 1 Interacts with Ribonucleoprotein Complexes To Enhance Infectious Bursal Disease Virus Polymerase Activity

Abstract: Infectious bursal disease virus (IBDV) is a double-stranded RNA (dsRNA) virus. Segment A contains two overlapping open reading frames (ORFs), which encode viral proteins VP2, VP3, VP4, and VP5. Segment B contains one ORF and encodes the viral RNA-dependent RNA polymerase, VP1. IBDV ribonucleoprotein complexes are composed of VP1, VP3, and dsRNA and play a critical role in mediating viral replication and transcription during the virus life cycle. In the present study, we identified a cellular factor, VDAC1, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 43 publications
(48 reference statements)
1
19
0
1
Order By: Relevance
“…Combining the protein functional analysis in the current study with previous reports (Dumas et al, 2015;Jovasevic et al, 2015;Han et al, 2017), we also observed that MAPRE1 and VDAC1 were related to virus infection. MAPRE1, also known as endbinding protein 1 (EB1), acts as a master regulator of plus-end tracking proteins (+TIPs) networks by targeting the growing ends of microtubules and recruiting other + TIPs and finally regulates the microtubule dynamics (Galjart, 2010).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Combining the protein functional analysis in the current study with previous reports (Dumas et al, 2015;Jovasevic et al, 2015;Han et al, 2017), we also observed that MAPRE1 and VDAC1 were related to virus infection. MAPRE1, also known as endbinding protein 1 (EB1), acts as a master regulator of plus-end tracking proteins (+TIPs) networks by targeting the growing ends of microtubules and recruiting other + TIPs and finally regulates the microtubule dynamics (Galjart, 2010).…”
Section: Discussionsupporting
confidence: 82%
“…VDAC1 was also involved in the infection of viruses, such as infectious bursal disease virus (IBDV). VDAC1 could interact with IBDV Ribonucleoprotein (RNPs) and facilitates IBDV replication by enhancing IBDV polymerase activity (Han et al, 2017). In our previous work, we have confirmed that CSFV infection was closely associated with mitochondrial function (Gou et al, 2017;Ma et al, 2019).…”
Section: Discussionmentioning
confidence: 60%
“…Gef1p Cl - silencing, a homologue of the mammalian CLC proteins in yeast, inhibited replication through its downstream effects on Cu 2+ homoeostasis, inhibiting the functionality of the viral replicase. Direct interaction of the voltage-dependent anion channel 1 with VP1 and VP3 of infectious bursal disease virus (family Birnavirdae ) was shown to stabilize the ribonucleoprotein complex, allowing full activity of the viral polymerase [38]. It may be possible that CLIC1, as an nsP3 interacting protein, is required for CHIKV genome replication for a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Han et al showed that knockdown of VDAC1 inhibited IBDV replication through the reduction of viral polymerase activity, and that the overexpression of VDAC1 promotes polymerase activity. Immunoprecipitation (IP) experiments showed that VDAC1 interacts with IBDV VP1 and VP3, components of RNPs, indicating a role for this channel in RNP formation [64].…”
Section: − Channels or Other Anions And Vials Replicationmentioning
confidence: 99%